Research on the influence of family capital on academic achievement of first-generation college students in China - Zhao, Ying; Wang, Zhi; Ren, Zengyuan (Frontiers in Psychology, 2023)
Based on the academic achievement data of college students of five universities in Liaoning Province, this paper used structural equation model to analyze the effect of family capital on the academic achievement of first-generation college students in depth. The study finds that the overall academic achievement of first-generation college students is at a moderate lower level, and it cannot leave without the influence of family capital and other predispositions. In terms of the effect path, cultural capital has the greatest impact on the overall level of academic achievement of first-generation college students, economic capital has a significant impact on students’ ability development, and social capital has a salient impact on students’ self-concept. Based on the study, we seek to bridge the gap of preconditions and promote the development of academic achievement of first-generation college students by paying special attention to the internal actions of student in higher education fields, and strengthening the connection between different fields, and implementing humanistic care for disadvantaged groups.